Investigating the Effect of Look-Ahead Distance on Automated Steering Performance - Sever, Mert; Zengin, Namik; Kirli, Ahmet; Arslanl, M. Selcuk (IEEE, 2018)
In this study, effect of look ahead distance on autonomous vehicle control is investigated. A simple output feedback control law with feedback of lateral and heading error at preview distance, is employed to analyze closed loop behavior against various look ahead distance, l(s) values. Firstly, analysis are performed with linearized vehicle model in complex domain with closed-loop pole properties such as settling time and damping ratio. Then, automated lane change performance is investigated in time domain. Throughout the simulation studies, a nonlinear vehicle model with 3 degrees-of-freedom yaw plane dynamics having nonlinear magic formula tire model is used. Allowable range of look ahead distance l(s) is investigated in terms of stability, safety/comfort and lane change performance. Stability analysis are performed with closed loop pole locations in complex plane for l(s) values in the range of 0 25 [m]. Safety/comfort analysis are performed with automated lane change maneuver by comparing peak values of lateral acceleration and side slip angle for l(s) values in the range of 2 25 [m]. Lane change performance is analyzed with the peak values of lateral distance overshoot and steering command magnitudes for l(s) values in the range of 2 - 25 [m].
Keywords: look-ahead distance; automated steering; parametric study; autonomous vehicles; LATERAL CONTROL; Automation & Control Systems; Computer Science; Engineering